Implementasi Program Kegiatan Organisasi Rohis Terhadap Pengetahuan Al-Qur’an Peserta Didik Di SMAN 1 Medang Deras Kabupaten Batu Bara - Tambunan, Siti Rahayu; Dawud Faza, Abrar M.; Yuzaidi, Yuzaidi (Kamaya: Jurnal Ilmu Agama, 2024)
This study is motivated by the low level of student participation in Rohis activities because there are some students who have limited knowledge about the Qur'an, not only in reading skills, but also in memorisation, and understanding the content. Rohis (Rohani Islam) is a platform that facilitates the development of students' knowledge and understanding of Islamic teachings, especially the Qur'an, through various activity programmes. The purpose of this study is to find out how the Rohis programme at SMAN 1 Medang Deras helps students understand the Qur'an better. Through descriptive qualitative approach, this research observed various Rohis activities, including tafsir study, tahfizh and Islamic discussion. Data were collected through observation techniques and in-depth interviews with Rohis students, as well as document analysis. The results showed that activities such as tafsir discussions, memorising verses, and active participation in positive groups deepen students' understanding of the Qur'an. In addition, students' active participation in Rohis also plays a role in strengthening their spiritual and moral values. This can be seen from the students' significant improvement in their ability to understand, memorise, and apply the teachings of the Qur'an after joining Rohis. It can be concluded that the Rohis programme succeeded in creating a conducive environment for the improvement of understanding of the Qur'an and the formation of students' religious character at SMAN 1 Medang Deras. It is hoped that the Rohis programme at SMAN 1 Medang Deras will continue to be expanded and enriched with various activities that support the understanding and practice of the Qur'an for students as a whole.